Espectro de ação do gene MI-1.2 a Meloidogyne spp. e estudo de populações virulentas e avirulentas em tomateiro: caracterização histopatológica da interação planta-nematoide - Gabriel, Márcia (2020)
The tomato crop is parasitized by different pathogens, among them Root-knot nematodes (RKN), genus Meloidogyne, which have a wide geographical distribution, high reproductive capacity and cause great damage to the tomato crop, with losses ranging from 25-100%. Among the control methods against Meloidogyne spp., genetic resistance, with the use of resistant tomato cultivars and rootstocks, is the most efficient and recommended measure, in addition to not requiring a drastic change in crop management and to causing less environmental impact in the control of this endoparasite. The present thesis has as its general objective the study of the resistance spectrum of the Mi-1.2 gene and a possible suppression in tomato rootstocks of this gene’s resistance to Meloidogyne spp. in Rio Grande do Sul. It also aims to measure the resistance of seven tomato rootstocks with the Mi-1.2 gene and evaluate the reaction of a plant of the species Solanun arcanum, with Mi-9 gene Meloidogyne spp. populations, furthermore characterizing histologically the interaction between the rootstock - 'Guardião' and two populations of M. javanica (virulent and avirulent). The experiments were carried out in laboratory and greenhouse facilities. In the first study, the resistance conferred by the Mi-1.2 gene/locus was evaluated in populations of 15 Meloidogyne species occurring in Brazil, using tomato cultivars Santa Clara (susceptible homozygote) and Debora Plus (resistant heterozygote). Thus, it was possible to verify that in addition to the species M. javanica, M. incognita and M. arenaria, resistance mediated by the Mi-1.2 gene was also effective for M. ethiopica, M. exigua, M. hispanica, M. inornata, M izalcoensis, M. konaensis, M. luci, M. morocciensis, M. paranaensis and M. petuniae and ineffective for M. enterolobii and M. hapla. In the second study, through the biochemical characterization of α-esterase, the perineal pattern and pathogenicity test in a resistant rootstock, it was possible to identify a virulent population of M. javanica, infecting the root system of ‘Guardião’ rootstock, in a production area of tomato in Rio Grande do Sul. In the third study, seven tomato rootstocks characterized by PCR technique as homozygous and heterozygous at the Mi locus, when inoculated with avirulent and virulent populations of Meloidogyne spp., showed that the dosage of Mi alleles is associated with a reduced reproductive factor (RF), only for avirulent populations. Besides that, the variability observed in the RF values of M. javanica, M. incognita and M. arenaria avirulent populations, within the Mi-1.2 allelic conditions, indicates a gene dosing effect, as well as influence from the genetic background of the plant. In the study of the mechanisms of resistance (avirulent populations) and susceptibility (virulent populations), the second-stage juveniles (J2) of M. javanica virulent population penetrated, underwent three moults and completed the cycle developing in fertile adults, equally in both genotypes (susceptible and resistant), while for the avirulent population of M. javanica, few J2s managed to penetrate the resistant genotype, and cell death and hypersensitivity reaction were visualized at the nematode infection site. In the fourth study, when evaluating the resistance of a new Mi-9 resistance gene, the results indicated resistance of the gene to M. javanica, M. incognita and M. arenaria populations. They also indicated susceptibility with population reduction for M. enterolobii and virulent Mi-1.2 of M. javanica, indicating that the resistance mediated by the Mi-9 gene does not differ completely from the Mi-1.2 gene at a temperature of 25-28ºC. These results show that the continuous search for new sources of resistance is indispensable, since plants with resistance to M. enterolobii and virulent Mi-1.2 RKN populations have not yet been found.